Analisis Hukum Penggunaan Kendaraan Pribadi Yang Digunakan Sebagai Angkutan Barang - Dede Amirudin; Ika Dewi Sartika Saimima (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
Abstract Since the dawn of civilization, people have relied on transportation as a means of moving from one place to another. When used in this way, shippers provide services to those in need and are helpful for the delivery of commodities as well as the movement of people. The problem under study concerns private vehicles and the limitations imposed on efforts to control and utilize private vehicles that do not have permission to operate as freight transport as they should be controlled according to Law Number 22 of 2009 concerning Road Traffic and Transportation. This research method is written using normative legal research methodology. To obtain data, conducted interviews and literature studies. Data collection will later be examined using logical, orderly, and systematic language descriptions. According to research findings, using private transportation as a means of transporting goods is a violation of law and a violationn of Law no. 22 of 22009, which is subject to both administrative and criminal sanctions. Keywords: private vehicle, law, freight transport